2021
DOI: 10.1108/aea-05-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of global economic policy uncertainty and the long-term bond yields on oil prices

Abstract: Purpose Might the impact of the global economic policy uncertainty (GEPU) and the long-term bond yields on oil prices be asymmetric? This paper aims to consider the effects of the GEPU and the US long-term government bond yields on oil prices using quantile-based analysis and nonlinear vector autoregression (VAR) model. The author hypothesized whether the negative and positive changes in the GEPU and the long-term bond yields of the USA have different effects on oil prices. Design/methodology/approach To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…To specify the empirical model in the most appropriate way, we first study the statistical summary of the variables ( 5% significance level, suggesting the applicability of the quantile analysis (Nusair & Olson, 2019;Ahmed et al, 2020;Chang et al, 2020;Ozcelebi, 2021). At this point, we examine the unit root properties of the variables through the quantile unit root test to avoid biased results and ensure a robust inference through a quantile approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To specify the empirical model in the most appropriate way, we first study the statistical summary of the variables ( 5% significance level, suggesting the applicability of the quantile analysis (Nusair & Olson, 2019;Ahmed et al, 2020;Chang et al, 2020;Ozcelebi, 2021). At this point, we examine the unit root properties of the variables through the quantile unit root test to avoid biased results and ensure a robust inference through a quantile approach.…”
Section: Resultsmentioning
confidence: 99%
“…We employ empirical models incorporating the role of regime changes and asymmetry in this study because Sarwar (2012) revealed that the relationships between financial stress and stock returns, as well as the impacts of the VIX on stock returns, are asymmetrical. Thus, this study differs from those by Abakah et al (2021) and Caraiani and Cǎlin (2020) in assuming that the cointegration relationship between the variables changes over the distribution and exposes the role of all quantiles of the distribution, in line with Ozcelebi (2021) and Troster et al (2018). The asymmetrical effects of the immediate interest rate of the United States and the VIX are also investigated with a quantile regression model that contains decomposed variables for positive and negative changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The VAR model is specified as a dynamic system of simultaneous equations between the copper price logarithm and the building permit series logarithm-previously transformed into 12-month moving averages (proxy variable of the effective real estate investment) (Ozcelebi 2021). Formally, we have:…”
Section: The Var Modelmentioning
confidence: 99%
“…Therefore, building permits can be considered a leading investment indicator for the real estate sector. The objective of this study is to answer the questions initially posed through a model that captures the dynamic relationship between the copper price and house building permits approved in the north of Chile, using the impulse-response functions of a vector autoregressive (VAR) model (Ozcelebi 2021). This way, our VAR model's impulse response functions aim to collect the short-term transmission mechanism of the international copper price in real estate investments reflected in new housing permits.…”
Section: Introductionmentioning
confidence: 99%
“…Oil stands as one of the most strategic commodities for the global economy, but it has become more volatile in recent decades due to a number of geopolitical issues, such as different conflicts in the Middle East, the global financial crisis of 2008–2010, the Russia–Ukraine dispute and frequent changes in global demand and supply of oil. (Arouri and Rault, 2011; Mohaddes and Raissi, 2019; Ozcelebi, 2021). The importance of oil for the world economy is further corroborated by the fact that the global oil market is worths over US$1.7tn (Nasir et al , 2018).…”
Section: Introductionmentioning
confidence: 99%